Synthesis of novel ferulic acid – based mannich bases - Vu, Tran Khac; Patil, Prakash (Vietnam Journal of Chemistry, 2014)
The synthesis of novel Mannich bases based on Ferulic acid is described. Ferulic acid (1) was first reacted with propargyl bromide and propargyl amine to give intermediates 2a and 2b, respectively. Next, the Mannich reaction of 2a and 2b with secondary amines in ethanol at reflux condition furnished two series of novel Mannich bases in good yields, 3a-h and 4a-h. All synthesized compounds were structurally characterized using spectroscopic methods NMR and MS. Keywords: Ferulic acid, Mannich bases, secondary amines, propargyl bromide, propargyl amine